Geospatial Tool-Based Geomorphological Mapping of The Lower Kulsi Basin, India - Gitika Thakuriah (Geological Agency, 2023)
Detailed geomorphological map of a region provides necessary information on landforms to understand the variations of surface and subsurface processes. Geomorphological maps prepared based on a combined geospatial and field-observation approach are preliminary data for precise, prompt, and efficient watershed-level planning. The Kulsi is a significant left-bank tributary of the Brahmaputra. It has potential for agricultural, land, and water resources, but the region needs to catch up due to frequent climatic-geomorphic hazards. Therefore, this article aims to prepare an object-oriented detailed geomorphological map using geospatial tools. High-resolution satellite images and a digital elevation model were used to generate the detailed geomorphological map of the studied area. The resultant map is verified with extensive fieldwork. The investigated basin is characterized by structural and denudation hills, anthropogenetic escarpment; pediment plain, older and young alluvial plain; active and older flood plain; islands and sandbar deposits, and highly sinuous river and natural and artificial surface waterbodies. The research can contribute to local governments' and communities' land and water resource development plans. Keywords: geomorphology, morphometry, satellite image, Geographic Information System